PANCASILA SEBAGAI IDEOLOGI TERBUKA - Supriyatno, Arie (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2011)
Pancasila ideology of openness at the level of instrumental value does not mean that we also open ourselves to wawasanan ideology of communism. But instead requires you to be aware of our vulnerability, so that both consciously and unconsciously not to use the insights of doctrine, policy and strategy that is Marxism Leninism / Communism. Salain a feature of this ideology is the permanent contradiction minded about, about not being able to didamaikannya conflict that existed until one of the parties to the contrary completely destroyed. One of the characteristics that others should watch out for is penghalalan all means to achieve goals.